Adapting the Medium: Dynamics of Intermedial Adaptation in Contemporary Japanese Popular Visual Culture - Pusztai Beáta (Acta Universitatis Sapientiae: Film and Media Studies, 2015)
With respect to adaptation studies, contemporary Japanese popular culture signifies a unique case, as different types of media (be those textual, auditive, visual or audio-visual) are tightly intertwined through the “recycling” of successful characters and stories. As a result, a neatly woven net of intermedial adaptations has been formed - the core of this complex system being the manga-anime-live-action film “adaptational triangle.” On the one hand, the paper addresses the interplay of the various factors by which the very existence of this network is made possible, such as the distinctive cultural attitude to “originality,” the structure of the comics, animation and film industries, and finally, the role of fictitious genealogies of both traditional and contemporary media in the negotiation of national identity. On the other hand, the essay also considers some of the most significant thematic, narrative, and stylistic effects this close interconnectedness has on the individual medium. Special attention is being paid to the nascent trend of merging the adaptive medium with that of the original story (viewing adaptation as integration), apparent in contemporary manga-based live- action comedies, as the extreme case of intermedial adaptation. That is, when the aim of the adaptational process is no longer the transposition of the story but the adaptation (i.e. the incorporation) of the medium itself- elevating certain medium-specific devices into transmedial phenomena.